1992
DOI: 10.1037/0033-2909.112.2.310
|View full text |Cite
|
Sign up to set email alerts
|

Feeling good-doing good: A conceptual analysis of the mood at work-organizational spontaneity relationship.

Abstract: Five forms of organizational spontaneity are described (helping co-workers, protecting the organization, making constructive suggestions, developing oneself, and spreading goodwill). Organizational spontaneity is compared with the seemingly analogous constructs of organizational citizenship behavior and prosocial organizational behavior. Based on a selective review of the literature, a multilevel model of spontaneity is presented. Positive mood at work is a pivotal construct in the model and posited as the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
881
3
91

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,243 publications
(1,010 citation statements)
references
References 182 publications
(284 reference statements)
35
881
3
91
Order By: Relevance
“…In the past 20 years, increased attention has been given to describing aspects of individual job performance that fall outside the bounds of traditional conceptualizations of quantity or quality of task performance (see Podsakoff, MacKenzie, Paine, & Bachrach, 2000). Researchers have adopted a variety of different labels to describe these aspects, including organizational citizenship behavior (Organ, 1988;Smith et al, 1983), prosocial organizational behavior (Brief & Motowidlo, 1986), organizational spontaneity (George & Brief, 1992;George & Jones, 1997), contextual performance (Borman & Motowidlo, 1993;Motowidlo & van Scotter, 1994), and extrarole behavior (Van Dyne, Cummings, & McLean Parks, 1995;Van Dyne & LePine, 1998).…”
mentioning
confidence: 99%
“…In the past 20 years, increased attention has been given to describing aspects of individual job performance that fall outside the bounds of traditional conceptualizations of quantity or quality of task performance (see Podsakoff, MacKenzie, Paine, & Bachrach, 2000). Researchers have adopted a variety of different labels to describe these aspects, including organizational citizenship behavior (Organ, 1988;Smith et al, 1983), prosocial organizational behavior (Brief & Motowidlo, 1986), organizational spontaneity (George & Brief, 1992;George & Jones, 1997), contextual performance (Borman & Motowidlo, 1993;Motowidlo & van Scotter, 1994), and extrarole behavior (Van Dyne, Cummings, & McLean Parks, 1995;Van Dyne & LePine, 1998).…”
mentioning
confidence: 99%
“…Previous studies from different perspectives have shown that the perceived quality of the physical work environment have influenced in employees' job perception, satisfaction, psychological stress, attitudes and overall performance (Sundstrom et al, 1994;George and Brief, 1992;McGuire and McLaren, 2009;Thatcher and Milner, 2012;Vischer, 2007;Huang et al, 2004;Hwang and Kim, 2013;O'Neill, 2010;Carlopio, 1996;Al-Anzi, 2009;Hua et al, 2011;Davis et al, 2011). Briner (2000) suggested that the nature and arrangement of designing and furnishing a place influence the frequency and type of interaction that takes place in an environment.…”
Section: The Role Of Work Environment Design On Individual Attitude Amentioning
confidence: 99%
“…Pour cela, la capacité de contagion que (Hatfield, Cacioppo & Rapson, 1994. p. 5). Au travers de la cohésion qu'elle pourrait amplifier, elle favoriserait la performance par une émulation et coopération d'équipe, la spontanéité et la confiance (George, 1989 ;George et Brief, 1992 ;Jones et George, 1998). Les travaux de George (1989 ;1990) démontrent l'influence de l'humeur du groupe sur le comportement prosocial vis-à-vis des collègues, des clients et sur la performance et l'absentéisme.…”
Section: This Paper Presents Research Carried Out At Cirano and Aims unclassified